Angiotensin II inhibits P‐glycoprotein in intestinal epithelial cells. (1st July 2019) - Kumar, Anoop; Priyamvada, Shubha; Soni, Vikas; Anbazhagan, Arivarasu N.; Gujral, Tarunmeet; Gill, Ravinder K.; Alrefai, Waddah A.; Dudeja, Pradeep K.; Saksena, Seema
Abstract: Aim: P‐glycoprotein (Pgp/MDR1) plays a major role in intestinal homeostasis. Decrease in Pgp function and expression has been implicated in the pathogenesis of IBD. However, inhibitory mechanisms involved in the decrease of Pgp in inflammation are not fully understood. Angiotensin II (Ang II), a peptide hormone predominantly expressed in the epithelial cells of the crypt‐villus junction of the intestine, has been shown to exert pro‐inflammatory effects in the gut. It is increased in IBD patients and animals with experimental colitis. Whether Ang II directly influences Pgp is not known. Methods: Pgp activity was measured as verapamil‐sensitive 3 H‐digoxin flux. Pgp surface expression and exocytosis were measured by cell surface biotinylation studies. Signalling pathways were elucidated by Western blot analysis and pharmacological approaches. Results: Ang II (10 nM) significantly inhibited Pgp activity at 60 minutes. Ang II‐mediated effects on Pgp function were receptor‐mediated as the Ang II receptor 1 (ATR1) antagonist, losartan, blocked Pgp inhibition. Ang II effects on Pgp activity appeared to be mediated via PI3 kinase, p38 MAPK and Akt signalling. Ang II‐mediated inhibition of Pgp activity was associated with a decrease in the surface membrane expression of Pgp protein via decreased exocytosis and was found to be dependent on the Akt pathway. Short‐term treatment of Ang II (2 mg/kg b.wt., 2 hours) to mice also decreased the membrane expression of Pgp protein levels in ileum and colon. Conclusion: Our findings provide novel insights into the role of Ang II and ATR1 in decreasing Pgp expression in intestinal inflammation.